2017
DOI: 10.9734/ajrimps/2017/37210
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Urdu Version of the Self-efficacy for Managing Chronic Disease 6-item Scale for Patients with Hypertension in Quetta, Pakistan

Abstract: Aim: Assessment and enhancement of self efficacy can improve the self management behavior of hypertensive patients. The aim of present study is to translate self-efficacy for managing chronic disease 6-item scale (SEM-CD6) into Urdu and check its validity and reliability. Methodology: A questionnaire based, observational cross sectional study was designed and conducted from March to August 2017 in 5 different Hypertension clinics of Quetta, Pakistan. Instrument was first translated in to Urdu by Forward -Back … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…We also found a significantly higher self-efficacy score among both employed patients and those with higher educational level compared to unemployed and less educated patients, respectively. These results are in consistency with those of previous studies where similar associations were reported [27,29].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We also found a significantly higher self-efficacy score among both employed patients and those with higher educational level compared to unemployed and less educated patients, respectively. These results are in consistency with those of previous studies where similar associations were reported [27,29].…”
Section: Discussionsupporting
confidence: 94%
“…This association can also be attributed to the fact that people with higher BMI, in general, tend to be less physically active, which in turn can negatively affect their self-efficacy as was found in a previous study conducted in Nigeria [28]. This association between selfefficacy and physical exercise has also been reported in many studies including a study conducted in china [11] and a more recent study conducted in Pakistan [29].…”
Section: Discussionmentioning
confidence: 53%
“… 24 The translated Urdu version of DMSES (U-DMSES to be used in this study) was reported to have α = 0.93. 25 …”
Section: Methodsmentioning
confidence: 99%
“…24 The translated Urdu version of DMSES (U-DMSES to be used in this study) was reported to have α = 0.93. 25 Self-care behaviors will be measured on the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire. The SDSCA tool developed and revised by Toobert et al; is a self-reported scale to measure self-care activities across diverse components of diabetes self-management.…”
Section: Measurement Toolsmentioning
confidence: 99%